Brain Herniation into Giant Arachnoid Granulation: An Unusual Case - Joana Ruivo Rodrigues; Gonçalo Roque Santos (Case Reports in Radiology)
Arachnoid granulations are structures filled with cerebrospinal fluid (CSF) that extend into the venous sinuses through openings in the dura mater and allow the drainage of CSF from subarachnoid space into venous system. Usually they are asymptomatic but can be symptomatic when large enough to cause sinus occlusion. We report a rare case of a brain herniation into a giant arachnoid granulation in an asymptomatic elderly male patient, which was discovered incidentally.